Isolation and multiplex genotyping of polymorphic microsatellite DNA markers in the snakehead murrel, Channa striata - Amirul Firdaus Jamaluddin Jamsari; Tan Min-Pau; Mohd Nor Siti-Azizah (Genetics and Molecular Biology, 2011)
Seven polymorphic microsatellite loci were isolated and characterized for the snakehead murrel, Channa striata (Channidae), a valuable tropical freshwater fish species. Among 25 specimens collected from Kedah state in Malaysia, the number of alleles per locus ranged from 2 to 7. Observed and expected heterozygosities ranged from 0.120 to 0.880 and 0.117 to 0.698, respectively. A single locus (CS1-C07) was significantly deviated from Hardy-Weinberg equilibrium after Bonferroni correction. These novel markers would be useful for population genetic studies of the C. striata.